The Effect Of Local Ingredients Based On The Physical-Mechanical Properties Of Ceramzite Concrete Based On Chemical Complex - Mirzaev Bakhodir Kozibaevich; Otakulov Bakhromjon Adhamovich; Mamatov Khamidulla Abdullaevich; Abdug'aniev Numonjon Nabijonovich; Solijonov Hojiakbar Solijon o‘g‘li (Genius Journals, 2023)
According to the results of the research conducted in this article, the introduction of complex chemical additives into the composition of expanded clay concrete mixtures significantly changes their properties. Complex chemical additives increase the properties of expanded clay concrete mixture, improve the properties of workability, reduce water demand.
Keywords: Expanded clay concrete; complex chemical additive; physical and mechanical properties